Adjuvant pembrolizumab versus placebo in resected stage III melanoma (EORTC 1325-MG/KEYNOTE-054): health-related quality-of-life results from a double-blind, randomised, controlled, phase 3 trial. Issue 5 (May 2021) - Bottomley, Andrew; Coens, Corneel; Mierzynska, Justyna; Blank, Christian U; Mandalà, Mario; Long, Georgina V; Atkinson, Victoria G; Dalle, Stéphane; Haydon, Andrew M; Meshcheryakov, Andrey; Khattak, Adnan; Carlino, Matteo S; et al.
Summary: Background: The European Organisation for Research and Treatment of Cancer (EORTC) 1325-MG/KEYNOTE-054 trial in patients with resected, high-risk stage III melanoma demonstrated improved recurrence-free survival with adjuvant pembrolizumab compared with placebo (hazard ratio 0·57 [98·4% CI 0·43–0·74]; p<0·0001). This study reports the results from the health-related quality-of-life (HRQOL) exploratory endpoint. Methods: This double-blind, randomised, controlled, phase 3 trial was done at 123 academic centres and community hospitals across 23 countries. Patients aged 18 years or older with previously untreated histologically confirmed stage IIIA, IIIB, or IIIC resected cutaneous melanoma, and an Eastern Cooperative Oncology Group performance status score of 1 or 0 were eligible. Patients were randomly assigned (1:1) using a central interactive voice-response system on the basis of a minimisation technique stratified for stage and geographic region to receive intravenously 200 mg pembrolizumab or placebo. Treatment was administered every 3 weeks for 1 year, or until disease recurrence, unacceptable toxicity, or death. The primary endpoint of the trial was recurrence-free survival (reported elsewhere). HRQOL was a prespecified exploratory endpoint, with global health/quality of life (GHQ) over 2 years measured by the EORTC QLQ-C30 as the primary analysis. Analyses were done in the intention-to-treat population. This study is registered with ClinicalTrials.gov, NCT02362594, and EudraCT, 2014-004944-37, and long-term follow-up is ongoing. Findings: Between Aug 26, 2015, and Nov 14, 2016, 1019 patients were assigned to pembrolizumab (n=514) or placebo (n=505). Median follow-up was 15·1 months (IQR 12·8–16·9) at the time of this analysis. HRQOL compliance was greater than 90% at baseline, greater than 70% during the first year, and greater than 60% thereafter for both groups. Because of low absolute compliance numbers at later follow-up, the analysis was truncated to week 84. Baseline GHQ scores were similar between groups (77·55 [SD 18·20] in the pembrolizumab group and 76·54 [17·81] in the placebo group) and remained stable over time. The difference in average GHQ score between the two groups over the 2 years was −2·2 points (95% CI −4·3 to −0·2). The difference in average score during treatment was −1·1 points (95% CI −3·2 to 0·9) and the difference in average score after treatment was −2·2 points (−4·8 to 0·4). These differences are within the 5-point clinical relevance threshold for the QLQ-C30 and are therefore clinically non-significant. Interpretation: Pembrolizumab does not result in a clinically significant decrease in HRQOL compared with placebo when given as adjuvant therapy for patients with resected, high-risk stage III melanoma. These results support the use of adjuvant pembrolizumab in this setting. Funding: Merck Sharp & Dohme.